Inovasi Pendidikan Islam - Hidayat, Syarif; Rukmanda, Meirani Rahayu (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Islamic education in the era of Industry 5.0 plays a central role in preparing the future generation to compete effectively amid rapid changes in the industry. Innovations in Islamic education, mainly through technology adoption, are crucial to providing a solid foundation for students. Integrating technology into teaching methods not only helps students understand technological developments but also assists them in instilling Islamic values while using technology. Developing a relevant and flexible curriculum becomes critical in facing globalization challenges and maintaining Islamic identity. Questions arise about how Islamic education can undergo a fundamental transformation to align Islamic teachings with the global dynamics driven by technology in the Industry 5.0 era. Additionally, how Islamic education can overcome the challenges of globalization, strengthen Islamic identity, and remain innovative by integrating technology in Industry 5.0 is a question that needs to be addressed. Furthermore, the role of technology in enhancing the quality of learning and the competence of teachers to shape a generation skilled in technology while also embodying the noble values of Islam in their actions and decisions is another question that needs answers. Therefore, this research aims to create creative and practical solutions to the challenges of Islamic education in the Industry 5.0 era through collaboration with industry and communities, enhancing teacher competence, and implementing technology that understands Islamic values. With this innovative approach, Islamic education can positively contribute to facing the developments in Industry 5.0 and producing a generation skilled in technology rooted in the noble values of Islam.